Secondary battery
Patent Information
- Application Number
- JP2022144702
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-12
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2042-09-12
AI Technical Summary
【0006】 本開示の二次電池は、析出型の金属リチウム負極を備え、且つ、クーロン効率が高い。
Smart Images

Figure 0007636378000002 
Figure 0007636378000003 
Figure 0007636378000004
Abstract
Description
[Technical field]
[0001] The present application discloses a secondary battery. [Background technology]
[0002] Patent Document 1 discloses a lithium solid-state battery comprising a positive electrode, a solid electrolyte layer, a negative electrode current collector, and metallic lithium as a negative electrode active material that is deposited between the solid electrolyte layer and the negative electrode current collector by charging, and a Li-absorption layer between the solid electrolyte layer and the negative electrode current collector. A carbon material is also disclosed as a Li-absorption material contained in the Li-absorption layer. Patent Document 2 discloses a solid-state battery comprising a positive electrode, a solid electrolyte layer, a negative electrode current collector, and metallic lithium as a negative electrode active material that is deposited between the solid electrolyte layer and the negative electrode current collector by charging, and a protective layer between the solid electrolyte layer and the negative electrode current collector. Also, Li2O, LiNbO3, and Li3PO4 are disclosed as materials contained in the protective layer. Patent Document 3 discloses a lithium metal composite electrode having a collector layer, a nucleation layer, and a metallic lithium layer in this order, or a collector layer, a metallic lithium layer, and a nucleation layer in this order. Furthermore, graphene, boron nitride, molybdenum oxide, and the like are disclosed as materials constituting the nucleation layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-036537 A [Patent Document 2] Patent Publication No. 2022-010554 [Patent Document 3] China Patent Publication No. 112117437 Summary of the Invention [Problem to be solved by the invention]
[0004] In secondary batteries equipped with a deposition-type metallic lithium negative electrode, metallic lithium is likely to be unevenly deposited between the electrolyte layer and the negative electrode current collector during charging, and the Coulombic efficiency during charging and discharging is likely to decrease. A new technology capable of increasing the Coulombic efficiency of secondary batteries equipped with a deposition-type metallic lithium negative electrode is needed. [Means for solving the problem]
[0005] The present application discloses the following aspects as means for solving the above problems. <Aspect 1> A secondary battery comprising: a positive electrode; an electrolyte layer; a negative electrode current collector; and metallic lithium as a negative electrode active material that is deposited between the electrolyte layer and the negative electrode current collector upon charging; an intermediate layer is present between the electrolyte layer and the negative electrode current collector; The intermediate layer comprises borohydride (HB); Secondary battery. <Aspect 2> The intermediate layer comprises borohydride (HB), a solid electrolyte and carbon; The secondary battery of embodiment 1. <Aspect 3> The solid electrolyte is a sulfide solid electrolyte. The secondary battery of embodiment 2. <Aspect 4> The intermediate layer covers a surface of the negative electrode current collector. The secondary battery according to any one of aspects 1 to 3. <Aspect 5> The electrolyte layer includes a sulfide solid electrolyte. The secondary battery according to any one of aspects 1 to 4. <Aspect 6> The negative electrode current collector comprises stainless steel. The secondary battery according to any one of aspects 1 to 5. Effect of the Invention
[0006] The secondary battery of the present disclosure includes a precipitated metallic lithium negative electrode and has high coulombic efficiency. [Brief description of the drawings]
[0007] [Figure 1] 1A and 1B show schematic configurations of a secondary battery 100 after charging and after discharging. [Diagram 2] The chemical structure of borohydride (HB) is shown. [Diagram 3] 1 shows an example of a flow of a manufacturing method for the secondary battery 100. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] 1. Secondary battery Hereinafter, a secondary battery according to an embodiment will be described with reference to the drawings, but the technology of the present disclosure is not limited to the following embodiment. FIG. 1 shows a configuration of a secondary battery 100 according to an embodiment. As shown in FIG. 1, the secondary battery 100 includes a positive electrode 10, an electrolyte layer 20, a negative electrode current collector 31, and metallic lithium 32 as a negative electrode active material that is deposited between the electrolyte layer 20 and the negative electrode current collector 31 by charging. An intermediate layer 33 is present between the electrolyte layer 20 and the negative electrode current collector 31. The intermediate layer 33 contains borohydride (HB).
[0009] 1.1 Positive electrode The positive electrode 10 includes at least a positive electrode active material. When the secondary battery 100 is charged, lithium ions released from the positive electrode active material reach between the electrolyte layer 20 and the negative electrode current collector 31 through the electrolyte layer 20, receive electrons, and are precipitated as metallic lithium 32. When the battery is discharged, the metallic lithium 32 between the electrolyte layer 20 and the negative electrode current collector 31 is dissolved (ionized) and returned to the positive electrode 10. The form of the positive electrode 10 may be any form known as a positive electrode for a secondary battery. For example, as shown in FIG. 1, the positive electrode 10 may include a positive electrode current collector 11 and a positive electrode active material layer 12.
[0010] 1.1.1 Positive electrode current collector The positive electrode collector 11 may be any material capable of functioning as a positive electrode collector of a secondary battery. The positive electrode collector 11 may be a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of ease of handling. The positive electrode collector 11 may be made of a plurality of metal foils. Examples of metals constituting the positive electrode collector 11 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, and stainless steel. In particular, the positive electrode collector 11 may contain Al from the viewpoint of ensuring oxidation resistance. The positive electrode collector 11 may have some kind of coating layer on its surface for the purpose of adjusting resistance, etc. In addition, when the positive electrode collector 11 is made of a plurality of metal foils, some kind of layer may be present between the plurality of metal foils. The thickness of the positive electrode collector 11 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.
[0011] 1.1.2 Cathode active material layer The positive electrode active material layer 12 includes a positive electrode active material, and may further include an electrolyte, a conductive assistant, a binder, and the like. Furthermore, the positive electrode active material layer 12 may include various additives. The content of each of the positive electrode active material, electrolyte, conductive assistant, binder, and the like in the positive electrode active material layer 12 may be appropriately determined according to the target battery performance. For example, the content of the positive electrode active material may be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and may be 100 mass% or less, or 90 mass% or less, assuming that the entire positive electrode active material layer 12 (total solid content) is 100 mass%. The shape of the positive electrode active material layer 12 is not particularly limited, and may be, for example, a sheet shape having a substantially flat surface. The thickness of the positive electrode active material layer 12 is not particularly limited and may be, for example, 0.1 μm or more, 1 μm or more, 10 μm or more, or 30 μm or more, and may be 2 mm or less, 1 mm or less, 500 μm or less, or 100 μm or less.
[0012] The positive electrode active material is a known positive electrode active material for secondary batteries, and any material capable of supplying lithium to the negative electrode side during charging may be used. For example, lithium cobalt oxide, lithium nickel oxide, LiNi1 / 3 Co 1 / 3 Mn 1 / 3 Various lithium-containing oxides such as O2, lithium manganate, and spinel-based lithium compounds can be used. Alternatively, a positive electrode active material in which lithium is absorbed in sulfur can be used. Only one type of positive electrode active material may be used alone, or two or more types may be used in combination. The positive electrode active material may be, for example, particulate, and the size is not particularly limited. The particles of the positive electrode active material may be solid particles, hollow particles, or particles having voids. The particles of the positive electrode active material may be primary particles, or secondary particles in which a plurality of primary particles are aggregated. The average particle diameter (D50) of the particles of the positive electrode active material may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. The average particle size D50 in the present application is the particle size (median size) at an integrated value of 50% in the volume-based particle size distribution determined by a laser diffraction / scattering method.
[0013] The surface of the positive electrode active material may be covered with a protective layer containing an ion-conductive oxide. That is, the positive electrode active material layer 12 may contain a composite having the above-mentioned positive electrode active material and a protective layer provided on the surface thereof. This makes it easier to suppress the reaction between the positive electrode active material and a sulfide (for example, a sulfide solid electrolyte described later). Examples of the ion-conductive oxide that covers and protects the surface of the positive electrode active material include Li3BO3, LiBO2, Li2CO3, LiAlO2, Li4SiO4, Li2SiO3, Li3PO4, Li2SO4, Li2TiO3, Li4Ti5O 12 , Li2Ti2O5, Li2ZrO3, LiNbO3, Li2MoO4, and Li2WO4. The coverage (area ratio) of the protective layer to the surface of the positive electrode active material may be, for example, 70% or more, 80% or more, or 90% or more. The thickness of the protective layer may be, for example, 0.1 nm or more or 1 nm or more, and may be 100 nm or less, or 20 nm or less.
[0014] The electrolyte that can be contained in the positive electrode active material layer 12 may be a solid electrolyte, a liquid electrolyte (electrolytic solution), or a combination thereof. In particular, when the positive electrode active material layer 12 contains a solid electrolyte (particularly, a sulfide solid electrolyte), the technology of the present disclosure can be expected to provide even greater effects.
[0015] The solid electrolyte may be any known solid electrolyte for secondary batteries. The solid electrolyte may be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, inorganic solid electrolytes have excellent ion conductivity and heat resistance. Examples of inorganic solid electrolytes include lithium lanthanum zirconate, LiPON, and Li 1+X Al X Ge 2-X Examples of the oxide solid electrolyte include (PO4)3, Li-SiO-based glass, and Li-Al-SO-based glass, and sulfide solid electrolytes such as Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5-GeS2. In particular, sulfide solid electrolytes, particularly sulfide solid electrolytes containing at least Li, S, and P as constituent elements, have high performance. The solid electrolyte may be amorphous or crystalline. The solid electrolyte may be, for example, particulate. Only one type of solid electrolyte may be used alone, or two or more types may be used in combination.
[0016] The electrolyte may contain, for example, lithium ions as carrier ions. The electrolyte may be, for example, a non-aqueous electrolyte. For example, the electrolyte may be a carbonate-based solvent in which a lithium salt is dissolved at a predetermined concentration. Examples of the carbonate-based solvent include fluoroethylene carbonate (FEC), ethylene carbonate (EC), and dimethyl carbonate (DMC). Examples of the lithium salt include hexafluorophosphate.
[0017] Examples of the conductive assistant that may be included in the positive electrode active material layer 12 include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, aluminum, and stainless steel. The conductive assistant may be, for example, particulate or fibrous, and the size is not particularly limited. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.
[0018] Examples of binders that can be included in the positive electrode active material layer 12 include butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, polyacrylic acid-based binders, etc. Only one type of binder may be used alone, or two or more types may be used in combination.
[0019] 1.2 Electrolyte layer The electrolyte layer 20 includes at least an electrolyte. The electrolyte layer 20 may include a solid electrolyte, and may further include a binder, various additives, and the like. The content of the electrolyte and the binder in the electrolyte layer 20 is not particularly limited. The electrolyte layer 20 may include a liquid component such as an electrolytic solution, or may not substantially include an electrolytic solution. The electrolyte layer 20 may have a separator or the like for preventing contact between the positive electrode and the negative electrode, and the electrolytic solution may be held in the separator. The thickness of the electrolyte layer 20 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0020] The electrolyte contained in the electrolyte layer 20 may be appropriately selected from those exemplified as electrolytes that may be contained in the positive electrode active material layer described above. In particular, when the electrolyte layer 20 contains a solid electrolyte (particularly, a sulfide solid electrolyte), a higher effect of the technology of the present disclosure can be expected. In addition, the binder that may be contained in the electrolyte layer 20 may be appropriately selected from those exemplified as binders that may be contained in the positive electrode active material layer described above. Each of the electrolyte and the binder may be used alone or in combination of two or more types. When the secondary battery is an electrolyte battery, the separator for holding the electrolyte may be any separator that is commonly used in secondary batteries, and examples of the separator include those made of resins such as polyethylene (PE), polypropylene (PP), polyester, and polyamide. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer structure separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be made of a nonwoven fabric such as a cellulose nonwoven fabric, a resin nonwoven fabric, or a glass fiber nonwoven fabric.
[0021] 1.3 Negative electrode current collector The negative electrode current collector 31 may be any material capable of functioning as a negative electrode current collector for a secondary battery. The negative electrode current collector 31 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, a metal foil is excellent in terms of ease of handling. The negative electrode current collector 31 may be made of a plurality of metal foils or sheets. Examples of metals constituting the negative electrode current collector 31 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring reduction resistance and being difficult to alloy with lithium, the negative electrode current collector 31 may be at least one metal selected from Cu, Ni, and stainless steel, and may include stainless steel in particular. The negative electrode current collector 31 may have some kind of coating layer on its surface. For example, as described later, an intermediate layer 33 containing borohydride (HB) may cover the surface of the negative electrode current collector 31. Alternatively, the negative electrode current collector 31 may have a coating layer other than the intermediate layer 33 on its surface. That is, a second intermediate layer may be present between the intermediate layer 33 and the negative electrode current collector 31. When the negative electrode current collector 31 is made of a plurality of metal foils, some layer may be present between the plurality of metal foils. The thickness of the negative electrode current collector 31 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.
[0022] 1.4 Metallic lithium as a negative electrode active material The secondary battery 100 includes a lithium deposition type negative electrode. Specifically, as shown in Fig. 1, metallic lithium 32 is deposited as a negative electrode active material between the electrolyte layer 20 and the negative electrode current collector 31 by charging. In this case, the metallic lithium 32 may be deposited as an alloy together with other metals. Furthermore, the metallic lithium 32 deposited between the electrolyte layer 20 and the negative electrode current collector 31 is dissolved (ionized) during discharge and returned to the positive electrode 10.
[0023] The amount of metallic lithium 32 precipitated between the electrolyte layer 20 and the negative electrode current collector 31 is not particularly limited. It may be adjusted appropriately depending on the target battery performance. However, if the amount of precipitated metallic lithium 32 is too large, there is a concern that pressure may be concentrated. In this regard, as a guideline for the amount of precipitated metallic lithium 32, it is recommended that the charge capacity of the secondary battery 100 is, for example, 1 mAh / cm. 2 More than 5mAh / cm 2 The amount may be such that:
[0024] According to the findings of the present inventor, a conventional secondary battery having a lithium precipitation type negative electrode has a problem that when metallic lithium is repeatedly precipitated and dissolved between the electrolyte layer and the negative electrode current collector, the metallic lithium is precipitated and dissolved non-uniformly, which reduces the Coulombic efficiency of the battery. In this regard, in order to improve the Coulombic efficiency of the battery, it is necessary to uniformly precipitate metallic lithium between the electrolyte layer and the negative electrode current collector during charging. In the secondary battery 100 of the present disclosure, by disposing the intermediate layer 33 between the electrolyte layer 20 and the negative electrode current collector 31, metallic lithium 32 can be easily precipitated uniformly between the electrolyte layer 20 and the negative electrode current collector 31.
[0025] 1.5 Middle Tier The intermediate layer 33 contains borohydride (HB). HB has H and B in a molar ratio of 1:1, and can be composed of a two-dimensional sheet skeleton of negatively charged boron and protons. HB is considered to have a two-dimensional structure as shown in FIG. 2 (Journal of the Crystallographic Society of Japan 64, 156-159 (2022)), and can have a microstructure in which two-dimensional structures as shown in FIG. 2 are stacked in layers. HB having such a structure has the function of absorbing (adsorbing) lithium during charging and releasing lithium during discharging. That is, during charging of the secondary battery 100, lithium ions supplied between the electrolyte layer 20 and the negative electrode current collector 31 are absorbed (adsorbed) by HB and gradually precipitate as metallic lithium 32. If the intermediate layer 33 does not exist and metallic lithium 32 is precipitated directly on the surface of the negative electrode current collector 31, the energy impact is large, and the precipitated metallic lithium 32 is likely to grow locally and rapidly. On the other hand, by the presence of the intermediate layer 33 containing HB between the electrolyte layer 20 and the negative electrode current collector 31, it is considered that during charging, some of the lithium ions are absorbed (adsorbed) by the HB and are gradually precipitated as metallic lithium 32, and the local growth of metallic lithium 32 is easily suppressed. Furthermore, during discharging of the secondary battery 100, the metallic lithium 32 between the electrolyte layer 20 and the negative electrode current collector 31 is dissolved (ionized) and returned to the positive electrode 10, and the lithium absorbed (adsorbed) by the HB of the intermediate layer 33 is also released from the HB and returned to the positive electrode 10. In other words, lithium can be reversibly precipitated and dissolved, and irreversible capacity is unlikely to occur. As a result of these, the coulombic efficiency of the secondary battery 100 is improved.
[0026] The intermediate layer 33 may be a layer made of borohydride (HB) alone, or may be a layer containing HB and other substances. For example, the content of HB in the intermediate layer 33 may be 10% by mass or more and 100% by mass or less, and the content of substances other than HB may be 0% by mass or more and 90% by mass or less. The content of HB in the intermediate layer 33 may be 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more, or 90% by mass or less, 80% by mass or less, 70% by mass or less, 60% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, or 20% by mass or less.
[0027] When the intermediate layer 33 is a layer made of HB only, it is considered that the surface properties of the intermediate layer 33 become more uniform, and metallic lithium 32 can be more uniformly precipitated during charging. On the other hand, even if the intermediate layer 33 is a layer containing a substance other than HB, it is considered that the above-mentioned effect of HB (the effect of slowly precipitating metallic lithium 32 while functioning as an occlusion (adsorption) site for lithium ions) is exhibited. Therefore, in order to exhibit some effect in addition to the above-mentioned effect of HB, the intermediate layer 33 may contain a substance other than HB. For example, when it is desired to impart high lithium ion conductivity or electronic conductivity to the intermediate layer 33, an electrolyte or a conductive assistant can be contained in the intermediate layer 33. Specifically, the intermediate layer 33 may contain borohydride (HB), a solid electrolyte, and a conductive assistant. The conductive assistant may be, for example, carbon. In addition, the solid electrolyte may be, for example, the inorganic solid electrolyte described above, in particular, a sulfide solid electrolyte.
[0028] As described above, the intermediate layer 33 may be present as a coating layer on the surface of the negative electrode current collector 31. That is, the intermediate layer 33 may cover the surface of the negative electrode current collector 31. In particular, when the intermediate layer 33 covers the entire surface of the negative electrode current collector 31, the deposition of metallic lithium 32 can be made more uniform.
[0029] The thickness of the intermediate layer 33 is not particularly limited and may be appropriately determined depending on the intended battery performance. For example, when it is determined that the ionic conductivity and electronic conductivity of the intermediate layer 33 are insufficient, the intermediate layer 33 may be thinned. Furthermore, when the intermediate layer 33 contains an electrolyte or a conductive assistant, the intermediate layer 33 may be thickened or thinned if sufficient ionic conductivity and electronic conductivity are ensured. The thickness of the intermediate layer 33 may be, for example, 1 nm or more and 1 mm or less. The thickness may be 10 nm or more or 100 nm or more, and may be 500 μm or less or 100 μm or less.
[0030] 1.6 Other materials The secondary battery 100 may have at least the above-mentioned components, and may further include other components. The components described below are examples of other components that the secondary battery 100 may have.
[0031] 1.6.1 Enclosure The secondary battery 100 may have each of the above-mentioned components housed inside an exterior body. More specifically, the portion excluding the tab or terminal for extracting power from the secondary battery 100 to the outside may be housed inside the exterior body. Any known exterior body for a battery may be adopted as the exterior body. For example, a laminate film may be used as the exterior body. Furthermore, a plurality of secondary batteries 100 may be electrically connected and arbitrarily stacked to form an assembled battery. In this case, the assembled battery may be housed inside a known battery case.
[0032] 1.6.2 Sealing resin In the secondary battery 100, each of the above components may be sealed with resin. For example, at least the side surfaces (surfaces along the stacking direction) of each layer shown in Fig. 1 may be sealed with resin. This makes it easier to prevent moisture from entering the inside of each layer. As the sealing resin, a known curable resin or thermoplastic resin may be used.
[0033] 1.6.3 Restraining members The secondary battery 100 may or may not have a restraining member for restraining each of the above components in the thickness direction. The internal resistance of the battery is easily reduced by applying a restraining pressure by the restraining member. There is no particular limit to the restraining pressure by the restraining member.
[0034] 2. Negative electrode current collector for lithium deposition type negative electrode The technology of the present disclosure also has an aspect as a negative electrode current collector for a lithium deposition type negative electrode. That is, the negative electrode current collector for a lithium deposition type negative electrode of the present disclosure has at least a part of its surface covered with a coating layer, and the coating layer contains borohydride (HB). As described above, the surface of the negative electrode current collector 31 is covered with a layer containing HB, so that local deposition and growth of metallic lithium 32 can be suppressed. There is no particular limitation on the method of covering the surface of the negative electrode current collector 31 with a coating layer. For example, a solution or slurry containing HB may be applied to the surface of the negative electrode current collector 31 and dried to form a coating layer on the surface of the negative electrode current collector 31. Alternatively, a sheet made of HB may be adhered or pressed to the surface of the negative electrode current collector 31.
[0035] 3. Manufacturing method of secondary battery The secondary battery 100 can be manufactured, for example, as follows. That is, as shown in FIG. 3, the method for manufacturing the secondary battery 100 according to the embodiment includes the following steps: At least one of the surface of the negative electrode current collector 31 and the surface of the electrolyte layer 20 is coated with a coating layer (intermediate layer 33) containing borohydride (HB) (FIG. 3(A)); Obtaining a laminate 50 having a positive electrode 10, the electrolyte layer 20, the coating layer (intermediate layer 33), and the negative electrode current collector 31 in this order by using the negative electrode current collector 31 or the electrolyte layer 20 coated with the coating layer (intermediate layer 33) ( FIG. 3(B) ); and The method includes charging the laminate 50 to deposit metallic lithium 32 between the electrolyte layer 20 and the negative electrode current collector 31 (FIG. 3(C)).
[0036] 3.1 Covering As shown in Fig. 3(A), in the manufacturing method according to this embodiment, at least one of the surface of the negative electrode current collector 31 and the surface of the electrolyte layer 20 is covered with a coating layer (intermediate layer 33) containing borohydride (HB). From the viewpoint of excellent handling properties, it is preferable that the surface of the negative electrode current collector 31 is coated with the coating layer as shown in Fig. 3(A). The method of coating the surface of the negative electrode current collector 31 and the surface of the electrolyte layer 20 with the coating layer is not particularly limited. For example, as described above, the coating layer can be formed on the surface of the negative electrode current collector 31 and / or the surface of the electrolyte layer 20 by a coating method using a solution or a slurry.
[0037] 3.2 Preparation of the laminate As shown in FIG. 3(B), in the manufacturing method according to the present embodiment, a laminate 50 having a positive electrode 10, an electrolyte layer 20, an intermediate layer 33, and a negative electrode collector 31 in this order is obtained using a negative electrode collector 31 and / or an electrolyte layer 20 coated with a coating layer (intermediate layer 33) as described above. The laminate 50 can be easily obtained by forming and laminating each of the above-mentioned materials by coating, transferring, adhering, or pressing the above-mentioned materials so that the above-mentioned positive electrode collector 11, positive electrode active material layer 12, electrolyte layer 20, intermediate layer 33, and negative electrode collector 31 are laminated in this order. The laminate 50 may include at least one each of the positive electrode collector 11, the positive electrode active material layer 12, the electrolyte layer 20, the intermediate layer 33, and the negative electrode collector 31. That is, the laminate 50 may have at least one laminate unit of the above-mentioned positive electrode current collector 11, positive electrode active material layer 12, electrolyte layer 20, intermediate layer 33, and negative electrode current collector 31, and may have a plurality of such laminate units. In this case, the plurality of laminate units may be electrically connected to each other in series, in parallel, or not electrically connected.
[0038] Before or after obtaining the laminate 50, pressure may be applied to each layer or laminate 50 in the thickness direction (stacking direction). For example, each layer constituting the laminate 50 may be pressed to be integrated, or gaps between each layer constituting the laminate 50 may be eliminated to reduce the interface resistance. Each layer or laminate 50 may be pressurized by a known means. For example, each layer or laminate 50 may be pressurized in the stacking direction by various pressing methods such as CIP, HIP, roll press, uniaxial press, and mold press. The magnitude of pressure in the stacking direction applied to each layer or laminate 50 may be appropriately determined according to the performance of the target battery. For example, when each layer or laminate 50 contains a sulfide solid electrolyte, the pressure may be 100 MPa or more, 150 MPa or more, 200 MPa or more, 250 MPa or more, 300 MPa or more, or 350 MPa or more from the viewpoint of easily performing the integration or elimination of the gaps by plastically deforming the sulfide solid electrolyte. The pressing time and pressing temperature of each layer or laminate 50 are not particularly limited.
[0039] 3.3 Charging As shown in FIG. 3(C), in the manufacturing method according to the present embodiment, the laminate 50 obtained as described above is charged, and metallic lithium 32 is precipitated between the electrolyte layer 20 and the negative electrode current collector 31. Specifically, by charging the laminate 50, lithium ions are conducted from the positive electrode active material contained in the positive electrode active material layer 12 to the negative electrode current collector 31 side through the electrolyte layer 20, and the lithium ions receive electrons between the electrolyte layer 20 and the negative electrode current collector 31, and are precipitated as metallic lithium 32. The charging may be the first charging after the preparation of the laminate 50, or may be the second or subsequent charging. The laminate 50 may be charged by a method similar to the charging method of a general battery. That is, charging may be performed by connecting an external power source to the positive electrode current collector 11 and the negative electrode current collector 31 of the laminate 50.
[0040] 3.4 Other processes The manufacturing method according to the present embodiment may include general steps for manufacturing a secondary battery in addition to the above-mentioned steps. For example, the steps include a step of housing the laminate 50 inside an exterior body such as a laminate film, a step of connecting a current collecting tab to the laminate 50, and the like. Specifically, for example, after connecting a current collecting tab to the current collectors 11 and 31 of the laminate 50 (parts of the current collectors 11 and 31 may be protruded and used as tabs), the laminate 50 may be housed in a laminate film as an exterior body, while the laminate film may be sealed with the tab pulled out to the outside of the laminate film, and then the laminate 50 may be charged via the tab outside the laminate film.
[0041] 4. Vehicles with secondary batteries As described above, the secondary battery of the present disclosure can deposit metallic lithium uniformly between the electrolyte layer and the negative electrode current collector, and has high Coulombic efficiency. That is, the secondary battery of the present disclosure has excellent durability. Such a secondary battery can be suitably used in at least one vehicle selected from, for example, a hybrid vehicle (HEV), a plug-in hybrid vehicle (PHEV), and an electric vehicle (BEV). That is, the technology of the present disclosure also has an aspect of a vehicle having a secondary battery, the secondary battery comprising a positive electrode, an electrolyte layer, a negative electrode current collector, and metallic lithium as a negative electrode active material deposited between the electrolyte layer and the negative electrode current collector by charging, and an intermediate layer is present between the electrolyte layer and the negative electrode current collector, and the intermediate layer contains borohydride (HB). Details of the configuration of the secondary battery are as described above. EXAMPLES
[0042] As described above, one embodiment of the technology of the present disclosure has been described, but the technology of the present disclosure can be modified in various ways other than the above embodiment without departing from the gist of the technology. The technology of the present disclosure will be described in more detail below while showing examples, but the technology of the present disclosure is not limited to the following examples.
[0043] 1. Preparation of HB-coated current collector A SUS foil (thickness: 10 μm) was attached to a platen with ethanol to remove air bubbles. Five drops of a solution of borohydride in acetonitrile were placed on the SUS foil using a dropper, and the foil was evenly coated using a doctor blade (gap: 25 μm). The foil was naturally dried until the liquid was gone, yielding a SUS current collector whose surface was coated with an HB layer (HB-coated current collector).
[0044] 2. Preparation of HB mixture 30 mg of borohydride, 60 mg of solid electrolyte (SE, LiBr-LiI-Li2S-P2S5), and 10 mg of conductive additive (VGCF) were dispersed in dehydrated heptane using an ultrasonic homogenizer. After that, the mixture was dried at 100°C for 1 hour to obtain an HB mixture.
[0045] 3. Preparation of Evaluation Cell A half cell was fabricated using metallic lithium as the counter electrode.
[0046] 3.1 Comparative Example 1 101.7 mg of solid electrolyte (LiBr-LiI-Li2S-P2S5) was placed in a φ11.28 mm cylinder and left to stand for 1 minute while applying a pressure of 6 tons to produce an electrolyte pellet. Metallic lithium foil (thickness: 150 μm) was placed on one side of the electrolyte pellet and left to stand for 1 minute while applying a pressure of 1 ton. Furthermore, SUS foil (φ11.28 mm) was placed on the other side of the electrolyte pellet and restrained with a torque of 2 Nm to obtain an evaluation cell.
[0047] 3.2 Example 1 An evaluation cell was obtained in the same manner as in the comparative example, except that the HB-coated current collector was used instead of the SUS foil. That is, in the evaluation cell according to Example 1, an intermediate layer made of HB was disposed between the electrolyte pellets and the SUS foil.
[0048] 3.3 Example 2 101.7 mg of solid electrolyte (LiBr-LiI-Li2S-P2S5) was put into a cylinder of φ11.28 mm, and the electrolyte pellet was prepared by leaving it for 1 minute while applying a pressure of 6 tons. 5 mg of the above HB mixture was put into one side of the electrolyte pellet, and the electrolyte-HB mixture pellet was obtained by leaving it for 1 minute while applying a pressure of 6 tons. Thereafter, a metal lithium foil (thickness 150 μm) was put into the other side of the electrolyte-HB mixture pellet, and the electrolyte-HB mixture pellet was left for 1 minute while applying a pressure of 1 ton. Furthermore, a SUS foil (φ11.28 mm) was placed on one side of the electrolyte-HB mixture pellet, and the pellet was restrained with a torque of 2 Nm to obtain an evaluation cell. That is, in the evaluation cell according to Example 2, an intermediate layer made of the HB mixture was arranged between the electrolyte pellet and the SUS foil.
[0049] 3.4 Comparative Example 2 An evaluation cell was obtained in the same manner as in Example 2, except that a mixture of a solid electrolyte and a conductive assistant (solid electrolyte:conductive assistant=60:10 (mass ratio)) was used instead of the HB mixture.
[0050] 4. Charge / discharge cycle test The fabricated evaluation cell was soaked in a thermostatic chamber at 25°C for 3 hours, then connected to a charge-discharge tester and charged at +1V to -1V, 0.435mA / cm while maintaining the temperature. 2 A cycle test was carried out at 100° C. The coulombic efficiency (the ratio of the discharge capacity to the charge capacity) was calculated for each of the first, second, and third cycles.
[0051] 5. Evaluation Results Table 1 below shows the type of intermediate layer between the solid electrolyte layer and the SUS foil and the results of the Coulombic efficiency for each of the examples and comparative examples.
[0052] [Table 1]
[0053] As is clear from the results shown in Table 1, when the intermediate layer between the electrolyte pellet and the SUS foil contains HB, the Coulomb efficiency is significantly increased. Specifically, the results are as follows. (1) When no intermediate layer is present as in Comparative Example 1 and metallic lithium is directly deposited on the surface of the SUS foil, the energy impact is large and the deposited metallic lithium tends to grow locally and rapidly. That is, metallic lithium is deposited non-uniformly, and many voids are formed, resulting in a decrease in Coulomb efficiency. (2) In contrast, as in Examples 1 and 2, the presence of an intermediate layer containing HB between the electrolyte pellet and the SUS foil is believed to cause a part of lithium to be absorbed (adsorbed) by HB during the precipitation of metallic lithium, and the lithium is gradually precipitated as metallic lithium, and local and rapid growth of metallic lithium is easily suppressed. In addition, when metallic lithium is dissolved (ionized), the lithium absorbed (adsorbed) by HB is also returned to the counter electrode. That is, in the evaluation cells according to Examples 1 and 2, the precipitation and dissolution of lithium are easily caused reversibly, and irreversible capacity is unlikely to occur. As a result of these, it is believed that the coulombic efficiency is improved. (3) When the intermediate layer contains only the solid electrolyte and VGCF but does not contain HB, as in Comparative Example 2, it is difficult to improve the Coulomb efficiency. This is thought to be because the unique effect of HB is not exerted.
[0054] In the above examples, a half cell was prepared using a metallic lithium foil as the counter electrode, and the evaluation was performed, but when actually constructing a secondary battery, an appropriate positive electrode may be used as the counter electrode. In addition, in the above examples, a specific solid electrolyte was used as the electrolyte layer, and SUS foil was used as the negative electrode current collector, but the type of electrolyte and the type of negative electrode current collector are not limited to these.
[0055] From the above results, it can be said that a secondary battery comprising a positive electrode, an electrolyte layer, a negative electrode current collector, and metallic lithium as a negative electrode active material that is precipitated between the electrolyte layer and the negative electrode current collector upon charging, in which an intermediate layer is present between the electrolyte layer and the negative electrode current collector, and in which the intermediate layer contains borohydride (HB) has high Coulombic efficiency. [Explanation of symbols]
[0056] 10 positive electrode 11 Positive electrode current collector 12 Cathode active material layer 20 Electrolyte layer 31 Negative electrode current collector 32 Metallic lithium 33 Middle Class 50 Laminate 100 Secondary battery
Claims
1. A secondary battery comprising: a positive electrode; an electrolyte layer; a negative electrode current collector; and metallic lithium as a negative electrode active material that is deposited between the electrolyte layer and the negative electrode current collector upon charging; an intermediate layer is present between the electrolyte layer and the negative electrode current collector; The intermediate layer comprises borohydride (HB); Secondary battery.
2. The intermediate layer comprises borohydride (HB), a solid electrolyte and carbon; The secondary battery according to claim 1 .
3. The solid electrolyte is a sulfide solid electrolyte. The secondary battery according to claim 2 .
4. The intermediate layer covers a surface of the negative electrode current collector. The secondary battery according to any one of claims 1 to 3.
5. The electrolyte layer includes a sulfide solid electrolyte. The secondary battery according to any one of claims 1 to 3.
6. The negative electrode current collector comprises stainless steel. The secondary battery according to any one of claims 1 to 3.
Citation Information
Patent Citations
Lithium metal composite electrode with controllable nucleation and growth of lithium metal and preparation method thereof
CN112117437A
Lithium solid battery
JP2019036537A
All-solid-state lithium battery and its manufacturing method
JP2021515353A
Solid battery
JP2022010554A